Breastfeeding supportive practices in European hospitals during the COVID-19 pandemic. (12th December 2022) - Merewood, Anne; Davanzo, Riccardo; Haas-Kogan, Maetal; Vertecchi, Giulia; Gizzi, Camilla; Mosca, Fabio; Burnham, Laura; Moretti, Corrado
Abstract: Introduction: During the first year of the COVID-19 pandemic, international recommendations and guidelines regarding breastfeeding-supportive hospital practices changed frequently. For example, some recommended separation of mothers and infants; others, feeding pumped milk instead of milk fed directly from the breast. Many recommendations were inconsistent or in direct conflict with each other. Guidance from UENPS (the Union of European Neonatal and Perinatal Societies) published in April 2020 recommended rooming in and direct breastfeeding where feasible, under strict measures of infection control, for women who were COVID-19 positive or under investigation for COVID-19. Key findings: Our study assessed data from respondents from 124 hospitals in 22 nations, with over 1000 births per year, who completed a survey on practices during the COVID-19 epidemic, as they related to the World Health Organization (WHO) Ten Steps to Successful Breastfeeding, considered to be the gold standard for breastfeeding support. The survey was conducted in the fall of 2020/winter of 2021. Overall 88% of responding hospitals had managed COVID positive mothers, and 7% had treated over 50 birthing women with confirmed COVID-19. The biggest change to hospital policy related to visitation policies, with 38% of hospitals disallowing all visitors for birthing women, and 19% shortening the postpartum stay. Eight hospitals (6%) recommended formula feeding instead of breastfeeding for women who tested positive for COVID-19 or were under investigation, whereas 73% continued to recommend direct, exclusive breastfeeding, but with some form of protection such as a mask or hand sanitizer for the mother or cleaning the breast before the feed. While 6% of hospitals discontinued rooming in, 31% strengthened their rooming in policy (keeping mothers and their babies together in the same room) to protect infants against possible exposure to the virus elsewhere in the hospital . Overall, 72% of hospitals used their country's national guidelines when making policy, 31% used WHO guidelines and 22% UENPS/SIN guidelines. Many European hospitals relied on more than one accredited source. Discussion: Our most concerning finding was that 6% of hospitals recommended formula feeding for COVID positive mothers, a measure that was later shown to be potentially harmful, as protection against the virus is transmitted through human milk. It is encouraging to note that a third of hospitals strengthened rooming in measures. Especially given the emergence of the highly transmissible Delta variant, the situation around postnatal care in maternity hospitals requires ongoing monitoring and may require proactive investment to regain pre-COVID era practices.